Changes of Chemical Composition and Aflatoxin Content of Peanut Products as Affected by Processing Methods - Erliana Ginting; Agustina Asri Rahmianna; Eriyanto Yusnawan (Buletin Palawija, 2019)
Peanut production in Indonesia is predominantly used for food, thus information on nutritional aspects and aflatoxin contamination in peanuts is essential in terms of food security and safety. As changes may occur during processing, the effects of processing methods on chemical composition and aflatoxin content in selected peanut products were studied. The dried peanut pods collected from a farmer in Ponorogo, East Java were stored for one month, and then the kernels were prepared into fried peanut (kacang goreng), peanut sauce (sambel pecel), peanut press cake (bungkil kacang), fried-pressed peanut (bungkil kacang goreng), fermented peanut press cake (tempe bungkil kacang), and fried peanut tempe (tempe bungkil kacang goreng). The trial was arranged in a randomized complete design with three replicates. ELISA method was applied for aflatoxin B1 analysis. The results showed that peanut kernels contained 26.3% protein (dw) and 50.4% fat (dw) with relatively low aflatoxin B1 content (9.1 ppb) due to low moisture level (5.6%), no Aspergillus flavus infection and high sound/intact kernels (73.1%). Peanuts processed into tempe bungkil kacang showed the highest increase in protein content, followed by tempe bungkil kacang goreng, bungkil kacang, and bungkil kacang goreng, while fat contents decreased in all products. Processing into kacang goreng and bungkil kacang goreng decreased aflatoxin B1 by 26.4% and 41.8%, respectively, while no significant differences were noted in sambal pecel and bungkil kacang. Aflatoxin B1 increased two-fold during the preparation of tempe bungkil kacang, however it significantly decreased by 38.9% after deep-fried. Excluding peanut tempe, all peanut products contained aflatoxin B1 below the permitted level (15 ppb), therefore they are safe for consumption.